The Influence of Content and Influencer Interaction on Followers' Trust in Social Media - Salbintan Fadilah Sari; Diana Fajarwati; Ika Baskara; Muhammad Arief (International Publisher (YAPENBI), 2025)
Study This investigate connection between Informational Support, Emotional Support, Influencer Credibility, Trust and Emotional Brand Attachment in the Sometinc Community . Study This use scale Likert five points For measure support social , credibility influencers , trust , and engagement emotional brand . The sample consists of from 145 customers Somethic skincare in Jabodetabek . Validity tested , reliability with Cronbach's Alpha , and data analysis using Partial Least Squares (PLS). Study This show that credibility influencer influence trust in community Somethinc . Owner brand can leveraging credible influencers For increase awareness brand , spread review positive , and strengthening trust . With choose the right influencer , owner brand can increase trust to Somethinc in various platform. The purpose of article This is For understand How trust towards social media influence attachment emotional to A brand through influencers .